Pharmacological Studies of Syrian Rue (Peganum harmala L., Zygophyllaceae) - Nazim A. Mamedov; Ardalan Pasdaran; Nilufer Z. Mamadalieva Mamadalieva (International Journal of Secondary Metabolite)
Syrian rue (Peganum harmala L., Zygophyllaceae) has been used in traditional medicine of Central Asia, the Middle East, and Caucasus areas (Azerbaijan) for centuries, mainly as ritual and psychedelic plant.  At full growth, this erect, dichotomously branched shrub is about 1 m in height with a dense foliage consisting of narrow, linear, pinnate leaves with acute spreading lobes, and small solitary, axillary, white flowers and globe capsules enclosing numerous angular seeds.  All parts of the plant (including roots) contain alkaloids.  The seeds contain β-carbolineses (harmine, harmalol and harman) with the active hallucinogen being the alkaloid harmine. The seeds contain a red pigment used for coloring wool and carpets and for use as a spice and, in traditional medicine, as valuable aphrodisiac.